Column amplification stages in CMOS image sensors based on incremental sigma-delta ADCs. (July 2021) - Freitas, Luis Miguel C.; Morgado-Dias, F.
Abstract: This paper focuses on the assessment of using programmable gain amplifiers on fast image sensor devices targeting low-light noise performance, comparing the responses of three on-chip column gain amplifier structures. Subsequent conclusions are derived from the usage of column amplifiers for imagers, retrieved from the comparison work. Based on the conducted study and the fabricated silicon device outputs, conclusive directions are pointed to determine the most optimal actions to adopt on future low-noise CMOS imagers. This work has revealed that the usage of amplification stages are essential for image sensors targeting low-noise, employing fast high-order incremental sigma-delta converters. Furthermore, the newest characterization results are also presented, done at a higher pixel supply voltage level. The measured performance improved from previous and early characterization, exhibiting 0.77% overall system non-linearity and featuring 2.91e-input-referred noise for the total readout chain noise at the same region of interest in the earlier work. Increasing the pixel supply has led to superior overall sensor performance. Graphical abstract: Image 1 Highlights: Externally supplied pixel reset voltage, led to superior overall sensor performance. The CIS featured above 105μ V / e - CG, 66.84dB DR, 38.35dB SNR and 6400e- Sat. Capacity. The CIS featured below 0.8% non-Linearity, and below 2.91e- input-referred noise. PGAs are essential for fast CIS, driving current hungry low-noise ISD converters. Single input CS Cascaded amplifiers are preferable than Differential input amplifiers.